Pengembangan Komik Online Mengenai Operasi Penjumlahan dan Pengurangan Bilangan Bulat dengan Model Neutralization On A Number Line - Endra Pratama; Puspita Sari; Swida Purwanto (Pendidikan Matematika FKIP Universitas Mataram, 2022)
The purpose of this research development is to develop an online comic product about the operation of calculating the addition and subtraction of integers for class VII with the Neutralization on a Number Line (NNL) model. This research is research and development (R&D) and uses Borg and Gall developmentmodel, which contains steps (1)Perform product analysis tobe developed, (2)Develop the initial product, (3) Expert validation and revision, (4)Small-scale field trials and product revisions, and (5) Large-scale field trials and final products. The research was conducted in January 2021 at SMP Negeri 2 East Karawang. Based on the results of research on learning media by material and language experts, and media experts obtained a percentage of 87% on all aspects of the material and language and 81% in all aspects of the media. Then, based on the results of field trials by teachers obtained a percentage of 89.6% in all aspects of materials, language, and media. Meanwhile, based on the results of field trials for students on a large scale, a percentage of 87.69% was obtained in all aspects of materials, language, and media. This research produced a product in the form of online comics about the operation of calculating the addition and subtraction of integers for class VII with the model Neutralization on a Number Line (NNL).